Identification of resistanceassociated proteins in closelyrelated maize lines varying in aflatoxin accumulation - Chen, Z.; Brown, R.L.; Menkir, A.; Cleveland, T.E. (Springer, 2012)
Aspergillus flavus infection of maize and subsequent contamination with carcinogenic aflatoxins poses serious health concerns, especially in developing countries. Maize lines resistant to A. flavus infection have been identified; however, the development of commercially-useful aflatoxin-resistant maize lines has been hindered due to a lack of breeding markers. To identify maize resistance-associated proteins (RAPs) as potential markers for breeding, 52 BC1S4 lines developed from crosses between five African maize inbreds and five temperate aflatoxin-resistant lines were screened using the kernel screening assay. Five pairs of closely-related lines that had 75–94% genetic similarity within each pair and which varied within each pair in aflatoxin accumulation were selected for proteomic investigation. Kernel embryo and endosperm protein profile differences within the pair and across pairs were compared using two-dimensional polyacrylamide gel electrophoresis. Differentially expressed (≥1.5-fold) RAPs were sequenced through tandem mass spectrometry and were identified as antifungal, stress-related, storage or regulatory proteins. Sequence homology analysis highlighted several proteins in maize that confer resistance to A. flavus infection and/or aflatoxin production.